Monitoring Impacts on Households in Lao PDR, Report No. 3, April-May 2021 : Results Snapshot from a Rapid Monitoring Phone Survey (Round 3) - World Bank (World Bank, Washington, DC, 2021)
As infections spiked across Southeast Asia, the number of confirmed cases in Lao PDR surged from fewer than 50 cases in early April to over 6,000 cases in August 2021. The government of Lao PDR announced a 14-day lockdown on April 22, 2021, which has since been extended several times. International borders remain closed. The measures have caused disruption to businesses and a reduction in working hours and labor earnings. The second Coronavirus (COVID-19) outbreak has setback economic recovery and much uncertainty remains. To monitor the social and economic impacts of the pandemic, the World Bank is conducting a series of Coronavirus (COVID-19) rapid monitoring phone surveys of households in Lao PDR. This monitoring data helps provide insights Into t e effects of the pandemic on household well-being. The third-round survey was conducted from April 26 to May 30, 2021 during a second lockdown. This note provides a snapshot of results from the third-round survey.